Modelling and simulation of integrated systems in engineering : issues of methodology, quality, testing and application - Murray-Smith, D. J. (David J.) (Woodhead Publishing, 2012)
This book places particular emphasis on issues of model quality and ideas of model testing and validation. Mathematical and computer-based models provide a foundation for explaining complex behaviour, decision-making, engineering design and for real-time simulators for research and training. Many engineering design techniques depend on suitable models, assessment of the adequacy of a given model for an intended application is therefore critically important. Generic model structures and dependable libraries of sub-models that can be applied repeatedly are increasingly important. Applications are drawn from the fields of mechanical, aeronautical and control engineering, and involve non-linear lumped-parameter models described by ordinary differential equations. Focuses on issues of model quality and the suitability of a given model for a specific applicationMultidisciplinary problems within engineering feature strongly in the applicationsThe development and testing of nonlinear dynamic models is given very strong emphasis.